The relationship between trustworthiness, congruence, likeability, and advertisement of celebrity endorsement in social media towards consumer purchasing intention - Cheah, Lee Suan (2022)
Celebrity endorsement is used by businesses to attract customer attention with the intention to lead them to make a purchase. Previous studies cover various group of customers and products. The purpose of this study is to investigate the relationship between trustworthiness, congruence, likeability, and advertisement of celebrity endorsement in the social media towards consumer purchasing intention. The target respondents are teachers in the state of Selangor. The questionnaire was developed from previous related study in celebrity endorsement. The questionnaire was distributed online, as it was during the Covid19 quarantine period. From the total received, only 200 questionnaires were useable. All respondents have at least one social media account and are exposed to advertisement endorsed by celebrity in the social media. Most of the respondents also follow at least one celebrity. The data collected are analysed using the SPSS version 26. All independent variables are positively and moderately related to consumer purchase intention. It can be concluded that celebrity endorsement is still impactful, even in social media platform, to attract consumers towards their product that could lead to product purchase eventually. Therefore, businesses should take advantage of celebrity endorsement to promote their products.